KOMUNIKASI KEBIJAKAN TERHADAP EFEKTIVITAS PENERTIBAN PEDAGANG KAKI LIMA DI KECAMATAN PANCA RIJANG - Askar Askar; Muhammad Ikbal; Kamaruddin sellang; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this study is to find out how Policy Communication on the Effectiveness of Controlling Street Vendors in Panca Rijang District, Sidenreng Rappang Regency and knowing the factors of Policy Communication on the Effectiveness of Controlling Street Vendors in Panca Rijang District, Sidenreng Rappang Regency.The research method used in this research is quantitative research, while the population in this study is 29,101 people. While the research sample is 97 people. The data collection technique used in this research is to use technique (1). Observation, (2). Questionnaire, (3). Documentation and (4) interviews. The collected data was then analyzed using a frequency table and using the SPSS application.The results of this study indicate that policy communication in Panca Rijang District, Sidenreng Rappang Regency can be categorized as Good Enough with a percentage of 65.4%, while the effectiveness of controlling street vendors in Panca Rijang District, Sidenreng Regency is Fairly Good with a percentage of 64.7%.